Clients and Consciousness: Drawing Militancy from Confusion on the Front Lines of the State - McElligott, Greg (Labour/Le Travailleur, 1997)
Abstract This article uses the experience of the Canada Employment and Immigration Union to argue that progressive political action is still possible on the front lines of the state. The CEIU has used client coalitions to defend and transform its membership, and these efforts have been aided by the contradictions of the neoconservative project itself. Union successes have occurred when clients and community groups are on side, real material gains are conceivable, and the issues at stake impinge on the discretionary decisions of front line workers. Union efforts are seen to constitute a prototypical strategy of "countermanagement," which can establish the foundations for a new, more democratically-accountable state.